Energy balance in the pole vault: effect of sex and level of performance - Frère, J.; Thiriot, H.; Potvin-Gilbert, M.; Sanchez, H.; Homo, S.; Cassirame, J. (Journal of Biomechanics, 2025)
Performance in pole vaulting is related to the athlete`s mechanical energy when crossing the bar, which corresponds to the sum of the energy during take-off (E-init) and the net energy gain during the pole support phase (E-gain). This study assessed the influence of sex and performance on the trade-off between the E-gain and E-init and aimed to identify the discriminating variables regardless of running speed. Eighty-four athletes were grouped by sex (female, male) and performance standards (inter-regional, national and international). Mechanical energy was computed from successful jumps video recorded in the sagittal plane. Correlations (r) between E-gain and E-init were assessed, and discriminant analysis identified how energy lost during take-off, pole plant timing, pole angle, take-off angle and maximal pole bending differentiated the groups. All correlations were negative (-0.87 < r < -0.41), and only the pole angle and pole plant timing differentiated the groups. The results suggested that each group faced an energy balance between E-gain and E-init, indicating multiple strategies to achieve similar performances. This study highlighted a hierarchy among the variables related to performance, with running speed (E-init) being prioritised, followed by a higher grip favouring E-gain.